Optimising Xpert-Ultra and culture testing to reliably measure tuberculosis prevalence in the community: findings from surveys in Zambia and South Africa. Issue 6 (16th June 2022) - Floyd, Sian; Klinkenberg, Eveline; de Haas, Petra; Kosloff, Barry; Gachie, Thomas; Dodd, Pete J; Ruperez, Maria; Wapamesa, Chali; Burnett, Michael J; Kalisvaart, Nico; Vermaak, Redwaan; Mainga, Tila; et al.
Abstract : Objectives: Prevalence surveys remain the best way to assess the national tuberculosis (TB) burden in many countries. Challenges with using culture (the reference standard) for TB diagnosis in prevalence surveys have led to increasing use of molecular tests (Xpert assays), but discordance between these two tests has created problems for deciding which individuals have TB. We aimed to design an accurate diagnostic algorithm for TB prevalence surveys (TBPS) that limits the use of culture. Design: TBPS in four communities, conducted during 2019. Setting: Three Zambian communities and one South-African community included in the TBPS of the Tuberculosis Reduction through Expanded Anti-retroviral Treatment and Screening study. Participants: Randomly sampled individuals aged ≥15 years. Among those who screened positive on chest X-ray or symptoms, two sputum samples were collected for field Xpert-Ultra testing and a third for laboratory liquid-culture testing. Clinicians reviewed screening and test results; in Zambia, participants with Mycobacterium tuberculosis -positive results were followed up 6–13 months later. Among 10 984 participants, 2092 screened positive, 1852 provided two samples for Xpert-Ultra testing, and 1009 had valid culture results. Outcomes: Culture and Xpert-Ultra test results. Results: Among 946 culture-negative individuals, 917 were Xpert-negative, 12 Xpert-trace-positive and 17 Xpert-positive (grade very low, low, medium or high), with Xpert categorised as the highest grade of the two sample results. Among 63 culture-positive individuals, 8 were Xpert-negative, 9 Xpert-trace-positive and 46 Xpert-positive. Counting trace-positive results as positive, the sensitivity of Xpert-Ultra compared with culture was 87% (95% CI 76% to 94%) using two samples compared with 76% (95% CI 64% to 86%) using one. Specificity was 97% when trace-positive results were counted as positive and 98% when trace-positive results were counted as negative. Most Xpert-Ultra-positive/culture-negative discordance was among individuals whose Xpert-positive results were trace-positive or very low grade or they reported previous TB treatment. Among individuals with both Xpert-Ultra results grade low or above, the positive-predictive-value was 90% (27/30); 3/30 were plausibly false-negative culture results. Conclusion: Using Xpert-Ultra as the primary diagnostic test in TBPS, with culture only for confirmatory testing, would identify a high proportion of TB cases while massively reducing survey culture requirements. Trial registration number: NCT03739736 .